Predicting the Microbiome and Metabolome Dynamics of Natural Apple Fermentation Towards the Development of Enhanced Functional Vinegar - Bruna Leal Maske; Ignácio Ruiz; Alexander da Silva Vale; Vitória de Mello Sampaio; Najua Kêmil El Kadri; Carlos Ricardo Soccol; Gilberto Vinícius Pereira (Fermentation)
Natural vinegar fermentation is a complex process influenced by the interplay between microbial communities and metabolites. This study examined the interplay between the microbiome and the metabolome over a three-month period, with samples collected every ten days. Using Illumina sequencing and chromatographic techniques (HPLC and GC-MS), we mapped microbial shifts and metabolite profiles. Early fermentation showed a diverse microbial presence, including genera such as Cronobacter, Luteibacter, and Saccharomyces. A stable microbial ecosystem established between days 15 and 70, characterized by the dominance of Leuconostoc, Gluconobacter, and Saccharomyces, which facilitated consistent substrate consumption and metabolite production, including various organic acids and ethanol. By day 70, Acetobacter prevalence increased significantly, correlating with a peak acetic acid production of 12.4 g/L. Correlation analyses revealed significant relationships between specific microbes and volatile organic compounds. This study highlights the crucial roles of these microbes in developing sensory profiles suited for industrial applications and proposes an optimal microbial consortium for enhancing vinegar quality. These data suggest that an optimal microbial consortium for vinegar fermentation should include Saccharomyces for efficient alcohol production, Leuconostoc for ester-mediated flavor complexity, and Acetobacter for robust acetic acid production. The presence of Komagataeibacter could further improve the sensory and functional qualities due to its role in producing bacterial cellulose.